Electric Power Supply of Meat Processing Enterprise through Utilization Heat of Compressor Station Secondary Energy Sources in Main Gasline - A. P. Nesenchuk; A. A. Abrazovsky; T. V. Ryzhova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2013)
The paper considers a structure of power consumption by a meat processing enterprise with indication of specific power consumption norms in accordance with product nomenclature. Schemes for supply of the enterprise with heat and cold through utilization of compressor station secondary energy sources in main gasline have been presented in the paper.